Architectural References within Émile Zola’s Novel, The Ladies’ Paradise - Layal Alsahli; Zeynep Tuna Ultav; Müge Sever (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
The depiction of space in literature is crucial to every story as it guides the reader’s imagination regarding the story’s location and the characters’ surroundings. This paper studies the relationship between architecture, interiors, and literary spaces by using a methodology that draws on architectural literary analysis, a methodology that uses literature as a medium to define and analyze architectural spaces and cues. Specifically, it investigates the connections between architectural and spatial references and their influences on societal concerns in literature – the literary space within The Ladies’ Paradise (1883), a novel by Émile Zola (1840-1902). The retail space portrayed within the novel dominates the narrative. Thus, the architectural spaces are described to support the storyline. These spatial cues indicate a specific overall theme, namely capitalism – an important issue to discuss within architectural discourse. Zola reveals a new perspective on the social and architectural impacts on society under capitalism through the public interior space of Ladies’ Paradise. The research also indicates the correlation between architecture, public space, and retailing culture through the birth of the “department store,” thus forever altering society’s ideology on retail culture. Although the novel is categorized as fictitious, the representation of 19th-century retailing culture, women’s role within society, and the significance of architecture are shown to be realistic to that time. In conclusion, this paper reveals the dialogue between architecture, societal gender issues, and the evolvement of retail culture through the medium of literature and derives lessons from this dialogue.